Analysis of Potential Value Chains for Scaling up Climate-Smart Agriculture in West Africa - Ouédraogo, Mathieu; Zougmoré, Robert B.; Partey, Samuel T. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Despite the development of several CSA options and their positive gains, their wide scale adoption remains a challenge. Integrating the value chain analysis into the Climate-Smart Village (CSV) - Agricultural Research for Development (AR4D) approach sounds positioning as an effective approach for upscaling of CSA.